Suprematic Architecture. Commitment to Excellence. Back to the Basics - Volchok, Yury P. (Actual Problems of Theory and History of Art, 2018)
The unique character of suprematic art is rooted in the perception of its author, K. S. Malevich, whose views developed to become the belief that it is necessary to create a suprematic method — the way of targeted movement towards perfection, constructed as a mental projection from the surface “painted on a canvas” onto the space of the world order. The article covers the establishment and the construction of the suprematic approach to the creative process fixed by K. S. Malevich in the beginning of the 1920s, on the background of the world perception at that time, based on logic patterns derived, first of all, from I. Kant’s philosophy, W. Windelband’s culturology, the theory of history by A. S. Lappo-Danilevskiy, tectology by A. A. Bogdanov, and B. P. Vysheslavtsev’s notion of “absolute”.The author attempts to comprehend the regularities accountable for interior logics of architecture’s “life and fate” implemented through “construction theory” methods. The construction theory is viewed in terms of Grand-Time architectonics and is perceived as applicable to architecture, as “an experiment on itself”.In this context, the history of contemporary architecture may be regarded as the “autobiography” of architectonic expertise during the whole of Grand Time — starting from the beginning of the 20th century, with an open ending date.
Keywords: architectonics; values; culture and civilization; culturology; suprematic architecture; theory of history; theory of building; artistic image; intellectual idea; commitment to excellence; raising to the extreme